NATURAL MATES OF NON-NULL FRENET CURVES IN MINKOWSKI 3-SPACE - Kelleci, Alev (Asia Pacific Academic, 2020)
In this paper, we define the natural mate of a non-null Frenet curve in Minkowski 3-spaces. The main aim of that paper is to find some relationships between a non-null Frenet curve and its natural mate. In this context, we obtain some results for the natural mate of a non-null Frenet curve to be a slant helix, a spherical curve, or a curve of constant curvature. Finally, as an application, we give an explicit example for natural mates. © 2020 Asia Pacific Journal of Mathematics.
Keywords: Minkowski space; natural mate; non-null curve; rectifying curves; slant helix; spherical curves